Pregnancy outcomes in patients with rheumatoid arthritis and systemic lupus erythematosus. Part II. Neonatal outcomes - E. V. Matyanova; N. M. Kosheleva; O. M. Kostareva; E. V. Fedorova; N. I. Klimenchenko (Научно-практическая ревматология, 2019)
Rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) are the most common autoimmune rheumatic diseases (RD) that occur mostly in women of childbearing age, and the occurrence of pregnancy is an expected fact. Due to the ongoing disputes over the ethics of maintaining birth rates among an unhealthy population, modern researchers focus attention on studies of the mutual impact of RD and pregnancy, on the safety of pharmacotherapy during conception and gestation, and on the health of the offspring born to female patients with RD.Objective: to evaluate the neonatal outcomes of pregnancy in patients with RA and SLE.Subjects and methods. An investigation was conducted to study the health status of 73 babies born to 72 female patients with RD (76 cases of pregnancy), of whom 29 patients with RA (32 cases of pregnancy) and 43 with SLE (44 cases of pregnancy) were followed up prospectively at the V.A. Nasonova Research Institute of Rheumatology and the Academician V.I. Kulakov National Medical Research Center of Obstetrics, Gynecology, and Perinatology. The health status of the babies was evaluated in the first year of their life. Supervising neonatologists and pediatricians recorded abnormalities in the newborns and subsequently analyzed using their medical records (extracts from maternity hospitals, children's hospitals, and outpatient cards).Results and discussion. Of the 76 supervised pregnancies, 72 (94.7%) resulted in 73 live births (one twin pregnancy in a patient with SLE). There were three (6.8%) cases of pregnancy loss in the second trimester in patients with SLE having antiphospholipid syndrome (APS) and one (3.1%) case of perinatal death (a boy and a girl from a monochorionic diamniotic twin with reversed arterial perfusion) in a patient with seropositive RA. The height and body weight of all the newborns conformed to gestational age. Patients with RA and SLE compared to the population more often gave birth to low birthweight babies (9.7 and 21.4% versus 60.9 per 1,000 live births in the Russian population). In the groups of mothers with RA and SLE, their infants had a high Apgar score of 8–9 at one and five minutes. Various abnormalities were detected in 5 (16.1%) and 15 (35.7%) babies born to mothers with RA and to those with SLE, respectively. Among the neonatal congenital anomalies (malformations), there was patent foramen ovale, patent ductus arteriosus, and hip joint dysplasia, which were more common in the babies born to mothers with SLE having APS and exceeded the population-based incidence of these anomalies. The babies were more commonly diagnosed with congenital pneumonia than those in the population; there were single cases of umbilical hernia, hemangioma, thrombocytopenia, hemorrhagic disease of the newborn, perinatal encephalopathy, and congenital hearing loss.Conclusion. The mothers with RA and SLE more often gave birth to low birthweight babies than did those in the population. The infants born to mothers with RA and SLE had significantly more frequently congenital heart defects (patent foramen ovale, patent ductus arteriosus) and congenital pneumonia. The detected abnormalities were more common in the newborns born to mothers with SLE having APS. Maternal RA and SLE activities and/or performed therapy were not found to have a negative impact on the incidence of abnormalities in babies.